The Historiographical Challenges Confronting Naga Christian Tribals Today - Khesoh, Mulehu (Utan Kayu Publishing, 2023)
Recently, the Naga scholars wrote their own stories using the stories written by the outsiders, quoting as though all of the stories were true. In doing so, they emulated their colonizers, and the latter’s half-truths further created a dilemma for the Naga people. Unless they tell their own stories, their stories will still be hidden and their traditional and cultural values cannot be restored. The coming of Western education and the Christian faith brought about tremendous changes in the Naga way of life and belief systems. This has also resulted in a drastic shift in the socio-cultural system. Modern education improves livelihood and health status. The spread of Christianity in Nagaland has both positive and negative impacts on Naga society. The changes are observed in the belief system, mindset, and attitudes of the people. Today many young people do not even remember the traditional stories, songs, and dances. They do not understand the significance of the patterns on their tribal shawls, nor do they revere nature as their ancestors did.